Pengaruh Price Earning Ratio (PER) Dan Earning Per Share (EPS) Terhadap Harga Saham Pada Perusahaan Sub Sektor Kosmetik Dan Keperluan Rumah Tangga Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2021 - Zulfa Nur Kholifah; Edi Murdiyanto; Zulfia Rahmawati (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
Every company really needs a price earning ratio which is used to assess whether shares are expensive or cheap based on the company in generating net profit and earnings per share are used to determine the valuation of the value of a company's shares with the aim of gaining profits for managers and shareholders. The aim of this research is to test and explain the influence of price earning ratio and earnings per shareon share prices in cosmetics and household goods sub-sector companies in 2015-2021. The sampling technique in this research used purposive sampling with a population of 9 companies listed on the Indonesian stock exchange using a sample of 5 companies in the cosmetics and household goods sub-sector for the 2015-2021 period using annual financial reports. From the analysis that has been carried out, the results of the research partially show that the price earnings ratio has no significant effect on share prices, which means that if PER increases, share prices will also increase, earnings per share have a significant effect on share prices, meaning that if EPS increases it will also affect an increase in share prices and simultaneously has a significant effect on share prices, meaning that together EPS and PER increase, this will have an impact on share price increases. This is known from the results of the following analysis: R2 value = 0.641031 or 64.1%, which means 35.9% is influenced by other variables outside the model.